The influence of the competence and training of state civil servants on work performance in the West Java provincial education office - Sri Mulyeni; Duddi Dermawan; Dika Nurdyansyah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
This study aims to test empirically competence and training on work performance in institution. This analysis uses independent variables, competency and performance. The dependent variabel is worK performance. The sample of this research are employees who work at the Education Office of West Java Province as many as 86. The sample was taken by purposive sampling metode. Data analysis using multiple linear regression analysis, by testing the hypothesis test statistic t. the results of this study indicate that competence significantly positively influences performance which ultimately leads to work performance. Based on hypothesis testing using the t test partially, it is obtained that H1 is rejected and H2 is accepted, which means that there is a positive and significant influence with a sig value of 0.000 < 0.005 between competency varables on training. The coefficient of determination (R2) is 0.487, meaning that the contribution of competence and training variabels to work performance variable is 0.487 or 48,7%, while the remaining 51,33% is influenced by other variables which are ignored or not examined in this study.